2023
DOI: 10.1039/d2ob02203f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis and antifouling activity of monoterpene–furan hybrid molecules

Abstract: Geraniol, a monoterpene, and furan are structural motifs that exhibit antifouling activity. In this study, monoterpene–furan hybrid molecules with potentially enhanced antifouling activity were designed and synthesized. The nine synthetic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…It was demonstrated that the broad-spectrum AF of this class of versatile compounds was dictated by the balance between hydrophobicity and cationic charge. Takamura, H et al synthesized nine monoterpene–furan hybrid molecules by inspiring the structure of geraniol (a naturally occurring monoterpene) and furan isolated from Mediterranean sponges ( Figure 5 ) [ 31 ]. These monoterpene–furan hybrids inhibited the settlement of the cypris larvae of the barnacle Balanus ( Amphibalanus ) amphitrite with EC 50 values of 1.65–4.70 μg·mL −1 .…”
Section: Compounds From Marine Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the broad-spectrum AF of this class of versatile compounds was dictated by the balance between hydrophobicity and cationic charge. Takamura, H et al synthesized nine monoterpene–furan hybrid molecules by inspiring the structure of geraniol (a naturally occurring monoterpene) and furan isolated from Mediterranean sponges ( Figure 5 ) [ 31 ]. These monoterpene–furan hybrids inhibited the settlement of the cypris larvae of the barnacle Balanus ( Amphibalanus ) amphitrite with EC 50 values of 1.65–4.70 μg·mL −1 .…”
Section: Compounds From Marine Organismsmentioning
confidence: 99%
“… The molecular structures of geraniol, dihydrofurospongin II, euryfuran and monoterpene-furan hybrid molecules [ 31 ]. …”
Section: Figurementioning
confidence: 99%
“…Thus, chemical synthesis studies should be expanded to facilitate the production of natural AF agents on larger scales. For instance, laboratory-produced monoterpene-furan geraniol hybrid molecules effectively suppressed cypris larvae of the barnacle Balanus Amphitrite more than the natural parent did [228].…”
Section: Obstacles Facing Commercial Use Of Natural Antifouling Agentsmentioning
confidence: 99%